Enhance student ict literacy and conceptual understanding using selm (simas eric learning model) - Ericka Darmawan; Giesty Trienita; Tri Asih Wahyu Hartati (Biosfer: Jurnal Pendidikan Biologi, 2023)
The Biology learning process at MAN 2 Surakarta has yet to be able to utilize technology as adequate learning support. Students still use their gadgets for things that are not related to learning. The assignments given by the teacher have yet to make much use of technology. An innovative learning model is needed to bridge technological advances in the learning process. SELM (Simas Eric Learning Model) is used in learning to determine the effect of the model on ICT literacy and conceptual understanding of class XI MAN 2 Surakarta students. There are two research instruments for ICT literacy using questionnaires and conceptual understanding using pretest and posttest on excretory system material. This study used a quasi-experimental research type with a pretest-posttest non-equivalent control group design. The data analysis technique was divided into two questionnaires using normative tests and a pretest and posttest using the N-Gain and sample tests. The results showed that the experimental class got an ICT literacy score of 81.5%, and the control class got 75%. The value of students' understanding of the concept of the experimental class got a score of 51.6%, and the control class got a score of 24.8%. The SELM is significant for increasing students' understanding of concepts and being able to increase students' ICT literacy.